Gasdermin D-mediated pyroptosis: mechanisms, diseases, and inhibitors - Dai, Zhen; Liu, Wan-Cong; Chen, Xiao-Yi; Wang, Xiao; Li, Jun-Long; Zhang, Xiang (Frontiers in Immunology, 2023)
Gasdermin D (GSDMD)-mediated pyroptosis and downstream inflammation are important self-protection mechanisms against stimuli and infections. Hosts can defend against intracellular bacterial infections by inducing cell pyroptosis, which triggers the clearance of pathogens. However, pyroptosis is a double-edged sword. Numerous studies have revealed the relationship between abnormal GSDMD activation and various inflammatory diseases, including sepsis, coronavirus disease 2019 (COVID-19), neurodegenerative diseases, nonalcoholic steatohepatitis (NASH), inflammatory bowel disease (IBD), and malignant tumors. GSDMD, a key pyroptosis-executing protein, is linked to inflammatory signal transduction, activation of various inflammasomes, and the release of downstream inflammatory cytokines. Thus, inhibiting GSDMD activation is considered an effective strategy for treating related inflammatory diseases. The study of the mechanism of GSDMD activation, the formation of GSDMD membrane pores, and the regulatory strategy of GSDMD-mediated pyroptosis is currently a hot topic. Moreover, studies of the structure of caspase-GSDMD complexes and more in-depth molecular mechanisms provide multiple strategies for the development of GSDMD inhibitors. This review will mainly discuss the structures of GSDMD and GSDMD pores, activation pathways, GSDMD-mediated diseases, and the development of GSDMD inhibitors.